Molecular Characterization of Two Mitogen-Activated Protein Kinases: p38 MAP Kinase and Ribosomal S6 Kinase From Bombyx mori (Lepidoptera: Bombycidae), and Insight Into Their Roles in Response to BmNPV Infection. Issue 1 (2nd February 2019) - Muhammad, Azharuddin; Toufeeq, Shahzad; Yu, Hai-Zhong; Wang, Jie; Zhang, Shang-Zhi; Li, Bing; Li, Zhen; Yang, Li-Ang; Hu, Pei; Ma, Yan; Xu, Jia-Ping
Abstract: Proteins p38 map kinase and ribosomal S6 kinase (S6K) as members of mitogen-activated protein kinases (MAPKs) play important roles against pathogens. In this study, Bmp38 and BmS6K were identified as differentially expressed proteins from iTRAQ database. Bmp38 and BmS6K were expressed, and recombinant proteins were purified. The bioinformatics analysis showed that both proteins have serine/threonine-protein kinases, catalytic domain (S_TKc) with 360 and 753 amino acids, respectively. The real-time quantitative polymerase chain reaction (RT-qPCR) results suggest that Bmp38 and BmS6K had high expression in the midgut and hemolymph. The comparative expression level of Bmp38 and BmS6K in BC9 was upregulated than in P50 in the midgut after Bombyx mori nucleopolyhedrovirus (BmNPV) infection. Western bolt results showed a positive correlation between RT-qPCR and iTRAQ data for Bmp38, but BmS6K data showed partial correlation with iTRAQ. Injection of anti-Bmp38 and anti-BmS6K serum suggested that Bmp38 may be involved against BmNPV infection, whereas BmS6K may require phosphorylation modification to inhibit BmNPV infection. Taken together, our results suggest that Bmp38 and BmS6k might play an important role in innate immunity of silkworm against BmNPV.